Heifers sired by bulls with low residual feed intake estimated breeding values have lower residual feed intake than heifers sired by bulls with high residual feed intake estimated breeding values - Minick Bormann, J.; Moser, Daniel W.; Marston, T.T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Feed is one of the largest costs in a cow/calf or feedlot operation. However, very little data is available to aid producers in genetically improving their herd for feed efficiency. In Australia, bull tests record individual feed intakes, which are used to calculate Estimated Breeding Values (EBV) (analogous to EPD) for residual feed intake (RFI). Residual feed intake measures the degree to which feed intake deviates from expected levels based on the animal size and rate of gain. Negative values are good; they indicate the animal ate less than expected for its size and growth rate. Our objective was to determine differences in feed efficiency traits of progeny from bulls with divergent genetic merit for RFI.
Keywords: Beef; Cattle; Estimated breeding values (EBV); Residual feed intake (RFI)